Waterlogging Effect on Growth, Yield and Physiological Responses of Blackgram (Vigna Mungo L.) Genotypes - Sayma Binta Alam; Nasrin Sultana; Saosan Zannat; Nazmun Naher (Journal of Agroforestry and Environment)
Waterlogging is one of the major abiotic stresses that affect growth, yield and physiological traits of blackgram. To evaluate the performance of six different blackgram genotypes imposed under waterlogging stress, a pot experiment was conducted in a two factor randomized complete block design with three replications in the Agroforestry and Environmental Science field lab at Sher-e-Bangla Agricultural University. Plastic pots with 30 days old plants were placed into a brick water chamber with waterlogging depth of 3-5 cm top of soils for 7 days to simulate waterlogging. Significant reduction was observed for plant height, number of leaves, SPAD value, nodule number, pod length, seeds per pod, yield per plant and the degree of reduction varied prominently over the blackgram genotypes. The number of leaves and SPAD value were higher in BARI Mash-3 which was 5.0 and 46.03 SPAD units in waterlogging situation. Among the six genotypes, BARI Mash-1 performed the best in respect of grain yield (5.04 g/plant) production followed by BARI Mash-3 (4.58 g/plant) under waterlogging condition. Stress tolerance index (STI) and yield index (YI) were highest in BARI Mash-2 (1.87) and BARI Mash-1 (1.67). Hence, these varieties can be added in the existing cropping pattern as a short-term waterlogging tolerant plant. In the future, waterlogging stress tolerant varieties with more suitable genetic base of blackgram plants needed to identify and utilize the novel traits of donors are now required in breeding programs.